POLITIK HUKUM PIDANA TERHADAP GAGALNYA MENDAFTAR CALON DPR/DPRD DALAM PEMILIHAN UMUM - Mohd. Yusuf D.M.; Fadhli Auliyah Muin; Hardiman Nainggolan; Roy Hakim Lubis; Muhammad Salim (The Juris, 2022)
Legal politics, namely as an effort to realize good regulations in accordance with the circumstances and situations at a time. As well as a policy from the state through the authorized bodies to establish the desired regulations, which are expected to be used to express, what is contained in society, and to achieve what is aspired. Diplomas are included in the part of educational instruments; therefore, the national education law also regulates the crime so that it can be charged with two articles (articles listed in the Criminal Code and articles listed in the National Education System Law). So, if the forged is a school diploma, it is more appropriate that what is imposed is an article in the National Education System Law. Indeed, in general it has been regulated in the Criminal Code, but for example the use of fake diplomas is not regulated in the National Education System Law by the Criminal Code with the term authentic letters/deeds being accommodated. The formulation of the problem in this study is how the politics of criminal law against the failure to register candidates for DPR/DPRD in the General Election. The method used is normative legal research. Based on the research results, it is known that the Politics of Criminal Law Against the Failure to Register Candidates for DPR/DPRD in the General Election that law is a political product that views law as a formalization or crystallization of interacting political wills.